The Use of Solar Power Plant Media to Increase Literacy Ability Solar Energy of Students - Sianturi, Manogari; Giawa, Etika Nyama; Faradiba; Masta, Ngia; Guswantoro, Taat; Murniarti, Erni (Journal of Education Reseach and Evaluation, 2024)
Indonesian students' science literacy level, especially in understanding solar energy as a renewable resource, still needs to be higher. This deficiency can be caused by various factors, including the need for more utilization of educational materials that aim to improve students' science literacy. The main objective of this study was to enhance students' solar energy literacy skills by applying solar power plant learning materials. Purposive sampling was used to select participants from two groups of students: Faculty of Teacher Training and Education (FKIP) and Faculty of Engineering (FT) who have completed physics of motion or introductory physics courses. FETT respondents numbered 33 people, consisting of 13 people from the Physics Education Study Program, 6 from the Chemistry Education Study Program, and 14 from the Biology Education Study Program. At the same time, The FT respondents were 23 students, consisting of 9 people from the Electrical Engineering Study Program and 14 from the Mechanical Engineering Study Program. Thus, the total number of respondents who met the criteria of this study amounted to 56 students. The assessment of solar energy literacy includes multiple-choice tests for cognitive aspects and questionnaires for affective and behavioral factors, which are managed through Google Forms. The provision of solar power plant learning modules increases knowledge, with the percentage of correct answers increasing in FKIP and FT students from pre-test to post-test. In conclusion, applying solar power plant learning materials can improve students' solar energy literacy skills.